Nikolai Ivanovich Pirogov (1810-1881): (To the 130th anniversary of the death): biobibliographic index / comp .:M.V.Mnichovich, N.A.Kozevskaya; Institute of Human Morphology, Russian Academy of Medical Sciences,. state. med. un-t them. acad. I.P. Pavlova. - Sapin, M. R.; Guminsky, Yu. I.; Makarova, O. V. (Морфологія / Morphologia / Morfologìâ, 2011)
The index includes materials about the life and activities of N.I. Pirogov, his scientific works, monographs and articles from journals and collections of works. The material is located in sections, within the section - according to the authors alphabet or work names. The material presented is checked by bibliographic sources and de visu, the numbering within each section. Bibliographic description of the works in accordance with GOST 7.1-2003 in the version that is acceptable for compilation of bibliographic indexes. The index is intended for scientists of the higher medical school, teachers, students and doctors.